2005
DOI: 10.1002/bdd.469
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dose pharmacokinetics of caffeine administered in chewing gum to normal healthy volunteers

Abstract: The results suggest that caffeine administered in the gum formulation (Stay Alert chewing gum) via a multiple dosing regimen provides an effective and convenient means of maintaining effective concentrations of caffeine that would in some operational scenarios be desirable for maintaining alertness and performance in sleep deprived individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 8 publications
1
28
1
Order By: Relevance
“…marksmanship), it has generally been concluded that caffeine enhances operational capabilities (McLellan et al, 2005a(McLellan et al, , 2005bTikuisis et al, 2004). This conclusion has prompted researchers to develop new methods, deemed more suitable than beverages, for delivering caffeine to personnel during active operations, and chewing gum has emerged as the preferred delivery vehicle (Kamimori et al, 2002;LaJambe et al, 2005;Syed et al, 2005).…”
Section: Caffeine Use In Military Operationsmentioning
confidence: 98%
“…marksmanship), it has generally been concluded that caffeine enhances operational capabilities (McLellan et al, 2005a(McLellan et al, , 2005bTikuisis et al, 2004). This conclusion has prompted researchers to develop new methods, deemed more suitable than beverages, for delivering caffeine to personnel during active operations, and chewing gum has emerged as the preferred delivery vehicle (Kamimori et al, 2002;LaJambe et al, 2005;Syed et al, 2005).…”
Section: Caffeine Use In Military Operationsmentioning
confidence: 98%
“…The concentration of caffeine in the body is modeled using a simplified convolution integral of an input and an elimination process ( Johnson and Straume, 1999; Johnson and Veldhuis, 1995; Syed et al ., 2005 Veldhuis et al ., 1987). The input process is approximated as an instantaneous dose i at time T i (the time of mastication), which allows the unbounded integral to be written as a sum of doses, one to N = 12.…”
Section: Methodsmentioning
confidence: 99%
“…Caffeine acts as a mild psycho-stimulant, being able to re-establish the alertness and performance capacity in subjects experiencing fatigue [1, 11]. The hepatic metabolism produces active metabolites (paraxanthine, theophylline, and theobromine) that contribute to pharmacologic effects [1, 11–13]. Caffeine contributes to competitive inhibition of phosphodiesterase by inactivating the cyclic adenosine monophosphate.…”
Section: Introductionmentioning
confidence: 99%